INFLUENCE OF PHYSICAL LOAD ON THE COGNITIVE SPHERE OF ATHLETES-ORENTERS - Zagorodnikova, D.M.; Kapilevich, L.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effect of physical activity on the cognitive sphere (memory, attention and thinking) in orienteers. Methods and structure of the study. The experiment involved male students of three specializations: "cross-country skiing", "general physical training" and "orienteering", aged 18 to 24 years, a total of 45 people. Students of the specializations "cross-country skiing" and "orienteering" attended training sessions in their sports more than five times a week from 60 to 120 minutes and were in the preparatory period of training. Students of the specialization "general physical training" attended classes at the university twice a week for 60 minutes. Results and conclusions. It was shown that the values ​​of cognitive qualities before the load differed insignificantly between the groups. The exception was the indicator of attention in terms of the number of errors - it was initially significantly lower in the group of orienteers than in both control groups. After physical activity, there was an improvement in most indicators in the group of orienteers, while in the control groups, an improvement was noted in only one indicator. The data obtained made it possible to conclude that orienteers, against the background of intense physical exertion, have an increase in indicators characterizing conative qualities. It can be assumed that this is the result of the formation of technical preparedness in this sport.